PUBLIC PREPAREDNESS FOR FACING EARTHQUAKE DISASTER IN LEMPUING AREA - Tuti Anggriani Utama; Rina Delfina; Nurmukaromatis Saleha (Universitas Bengkulu, 2019)
Disaster preparedness is a series of activities carried out to anticipate disasters through organizing and through appropriate and efficient steps. Bengkulu Province is one of the areas prone to earthquake disasters. One of them is the lempuing village located in the long coastal area of Bengkulu City, which is adjacent to a residential area of around 2 meters which has a very strong impact when the earthquake occurs. The purpose of this study was to describe community preparedness in the region of the earthquake against earthquake disasters. This type of research is descriptive research, the sample in this study was the head of the family taken by accidental sampling. The results of the study showed that the majority of respondents 66% with categories not ready for disaster. Researchers suggest that disaster preparedness needs to be improved in an effort to increase community preparedness in the face of disasters.